LAPORAN KASUS: DIABETES MELITUS TIPE 2, HIPERTENSI, DAN NEUROPATI DIABETIK PADA PASIEN LANJUT USIA - Tazkia Vidini Caya; Nanda Fitri Wardani (CV. Jasa Sukses Abadi, 2026)
Type 2 diabetes mellitus (T2DM) and hypertension are common chronic diseases among older adults and are associated with microvascular complications such as diabetic neuropathy. Comprehensive management is essential to prevent disease progression and improve patients' quality of life. This case report aims to describe the implementation of a holistic approach in managing a geriatric patient with T2DM, hypertension, and diabetic neuropathy at the primary healthcare level. Data were obtained through history taking, physical examination, laboratory findings, and follow-up evaluation. A 62-year-old woman presented with tingling and pain in both feet that had progressively worsened over the previous three months, accompanied by intermittent headaches. Clinical evaluation revealed a blood pressure of 160/95 mmHg, fasting blood glucose of 162 mg/dL, random blood glucose of 348 mg/dL, diminished patellar and Achilles reflexes, and a Douleur Neuropathique 4 (DN4) score of 5. The patient was diagnosed with T2DM, stage II hypertension, and diabetic neuropathy. Management included pharmacological treatment with metformin, amlodipine, and gabapentin, along with education regarding medication adherence, dietary modification, physical activity, and family support. Follow-up after 14 days demonstrated improvement in neuropathic symptoms, reduction of blood pressure to 137/90 mmHg, decreased fasting blood glucose to 149 mg/dL, improved treatment adherence, and healthier lifestyle behaviors. This case highlights that a holistic approach integrating medical therapy, health education, lifestyle modification, and family involvement can contribute to better clinical outcomes and risk factor control in geriatric patients with chronic diseases.